1990
DOI: 10.1016/0010-2180(90)90040-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse combustion: The quantification of characteristic times

Abstract: Measurements of the total ignition delay time in a pulse combustor have been made for several chemical kinetic ignition delay times and several fluid dynamic mixing times. These measured total ignition delay times are compared with calculated values of the characteristic time for mixing and with calculated values for the homogeneous ignition delay time. A chemical kinetic model was used to calculate the homogeneous chemical kinetic ignition delay time for conditions typical of an operating pulse combustor. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(21 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…noting the visual similarity between the 100 percent natural gas map For practical applications, these data suggest that it is important to at 339 K (150 F) (Figure 5c) and Figure 9. An exact characterization test combustor stability with a recognition that ambient conditions and of the reaction and advection times (as in Keller et al 1990) is needed fuel composition may play an important role. Operation of a comto make a definitive conclusion about the role of the reaction time.…”
Section: Fuel Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…noting the visual similarity between the 100 percent natural gas map For practical applications, these data suggest that it is important to at 339 K (150 F) (Figure 5c) and Figure 9. An exact characterization test combustor stability with a recognition that ambient conditions and of the reaction and advection times (as in Keller et al 1990) is needed fuel composition may play an important role. Operation of a comto make a definitive conclusion about the role of the reaction time.…”
Section: Fuel Compositionmentioning
confidence: 99%
“…After a short time, the nozzle velocity would again increase as the combustor pressure drops, thereby injecting the accumulated mixture from the nozzle into the flame. If the resulting heat release and pressure fluctuation are in phase, the oscillation will To interpret the data, we modify an approach described by Keller et al (1989Keller et al ( , 1990. Keller showed that oscillating, premixed (pulse) combustion could be characterized by a fluid dynamic mixing time and by a chemical reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of spontaneous ignition based on equation (6) has been presented by Kanury (1984). Keller et al (1990) have made a similar analysis for the combustion of methane gas. A simple one-step reaction rate model for CH,(g) as the fuel is…”
Section: Spontaneous Ignition Delaymentioning
confidence: 99%
“…The activation energy E is about 120 kJ/mol. According to the calculations made by Keller et al (1990), the magnitude of the chemical ignition delay time was 0.5-1.0 ms. Keller and Westbrook (1987) found that, if the chemical ignition time was too short, the pulse combustor did not operate stably.…”
Section: Spontaneous Ignition Delaymentioning
confidence: 99%
“…To interpret the data, we modify an approach described by Keller et al (1989Keller et al ( , 1990. Keller showed that oscillating, premixed (pulse) combustion mild be characterized by a fluid dynamic mixing time and by a chemical reaction time.…”
Section: Introductionmentioning
confidence: 99%